Peer Tutoring for Sustainable Biology Education: Enhancing Student Activity, Motivation, and Learning Outcomes in the Respiratory System Unit - Nurul Arini; Yusminah Hala; Rachmawaty; Firdaus Daud; Ismail (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effect of the peer tutoring method on learning activity, learning motivation, and biology learning outcomes of grade XI students at SMAN 15 Gowa. This quasi-experimental research employed a pretest-posttest control group design involving 54 students divided into experimental (n = 27) and control groups (n = 27). Learning activity was measured using observation sheets based on Paul B. Diedrich indicators, motivation was assessed through questionnaires using Keller's ARCS model, and learning outcomes were evaluated using cognitive tests consisting of 25 multiple-choice and 5 essay questions based on revised Bloom's taxonomy. Data were analyzed using Independent Samples t-test to compare groups and Paired Samples t-test to analyze improvements within groups, with a significance level of α = 0.05. The results showed significant effects of peer tutoring on learning activity (p = 0.015), motivation (p = 0.000), and learning outcomes (p = 0.000). The experimental group demonstrated higher mean scores in activity (25.93 vs 24.44) and substantial improvements in motivation (N-Gain 0.61, medium category vs 0.12, low category) and learning outcomes (N-Gain 0.57, medium category vs 0.29, low category). The mastery level achievement in the experimental group (92.60%) was substantially higher compared to the control group (66.70%). Superior performance can be attributed to enhanced peer interaction facilitating deeper conceptual understanding through social constructivism and the Zone of Proximal Development. These findings indicate that the peer tutoring method effectively enhances students' learning activity, motivation, and outcomes in complex biology topics, with practical implications for improving biology education quality at the secondary school level.